Influence of Political Cycles on Public Spending and its effect on Public Debt (Management and Connections Journal, 2022)
This study analyzes the influence of political budget cycles on municipal public spending and estimates its effect on local public debt. For this, data from the municipalities of Rio Grande do Sul, from 2005 to 2016, were analyzed using the panel data analysis technique. The results suggest that public expenditures impact the public debt of municipalities in Rio Grande do Sul and, when controlled by the political cycle, specifically in pre-election years, have a positive effect on public debt. This means that, in the year before the elections, the effect of public spending on municipal public debt increases. However, in the election year, this effect was not statistically significant. Regarding the partisan alignment of the municipal government with the federal government, the results were positive, so the fact that there is a coalition between municipal and federal governments increases public spending and tends to increase the public debt of municipalities.